1980
DOI: 10.1111/j.1445-2197.1980.tb04205.x
|View full text |Cite
|
Sign up to set email alerts
|

The Intraarterial Infusion of Chemotherapeutic Agents as “Basal” Treatment of Cancer: Evidence of Increased Drug Activity in Regionally Infused Tissues

Abstract: There is evidence from a number of centres that some forms of locally advanced and aggressive cancers which are difficult to eradicate by standard means can be reduced by the use 01 “basal” chemotherapy to a degree which will allow more certain tumour eradication by subsequent radiotherapy and/or surgery. Clinicians have been divided as to whether there is an advantage in giving the chemotherapeutic agents directly into a regional artery of supply where this is feasible, as opposed to their systemic administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Systemic side effects, including bone-marrow depression and gastrointestinal manifestations, are less frequent and less severe when the chemotherapeutic regimen is given intraarterially as compared to same doses of agents given intravenously [27]. The results of the present study showed that intraarterial chemotherapy was not followed by severe toxicity probably because the doses were lower than those used in systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 68%
“…Systemic side effects, including bone-marrow depression and gastrointestinal manifestations, are less frequent and less severe when the chemotherapeutic regimen is given intraarterially as compared to same doses of agents given intravenously [27]. The results of the present study showed that intraarterial chemotherapy was not followed by severe toxicity probably because the doses were lower than those used in systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 68%
“…The experience of the first years of application of intra-arterial chemotherapy made clear that initial tumor resection and irradiation significantly influences the vascular provision of the tumors. Thus, a higher effect of the chemotherapeutics could be achieved in cases of application as initial therapy with no prior surgery or irradiation possibly impairing the blood supply of the tumor [29]. Specific indications for the current therapy cannot be stated at this point, since we examined a limited number of patients who received different numbers of chemotherapy cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the target organ, the extraction rate may result in drug delivery that is many times higher than that achieved with standard intravenous therapy, and simultaneously associated with limited systemic toxic effects. 7,17 In addition, neoadjuvant chemotherapy, chemotherapy given prior to the "primary" or definitive treatment, induces tumor cell necrosis and potentially minimizes dissemination of viable tumor cells during the subsequent surgical manipulation. Finally, induction chemotherapy may induce a reduction in tumor size, rendering the mass more amenable to surgery.…”
Section: Methodsmentioning
confidence: 99%
“…First, a very high dose of drug is delivered to the target area. 7,17 This potentially enhances tumor cell kills by increasing area-under-curve concentration and shifting the dose-response curve to the right. Second, systemic toxic effects may be limited if a high percentage of the drug is removed as it passes through the target capillary bed and the remainder is diluted in the systemic circulation.…”
mentioning
confidence: 99%